Boosting the Redox Kinetics of High‐Voltage P2‐Type Cathode by Radially Oriented {010} Exposed Nanoplates for High‐Power Sodium‐Ion Batteries. Issue 1 (13th January 2022) - Li, Feng; Fan, Ke; Hou, Peiyu; Huang, Haitao
Abstract : Sodium‐Ion Batteries High‐voltage P2‐type cathodes suffer from sluggish reaction kinetics. In article number 2100123 by Peiyu Hou, Haitao Huang, and co‐workers, hierarchically assembled nanoplates with highly exposed {010} facets are designed to achieve high power density sodium‐ion batteries.